Bioinsecticides Production by Bacillus thuringiensis subsp. aizawai using Agroindustrial by-Product in Solid Fermentation - Kirana Sanggrami Sasmitaloka; Titi Candra Sunarti; Mulyorini Rahayuningsih (Jurnal Penelitian Pascapanen Pertanian, 2016)
Bacillus thuringiensis subsp. aizawai is one of well-known bioinsectiside resources, and utilized in organic farming for the replacement of chemical insecticide. The active compounds produced from fermentation process of B. thuringiensis subsp. aizawai are bacterial spores and protein crystal of δ-endotoxins, which are variously toxic to larvae of the Lepidoptera and Coleoptera. The use of bioinsecticides in Indonesia is still rarely because bioinsecticide marketed in Indonesia is still an import product so that price is relatively expensive. This problem can be overcome with producing bioinsecticide contain active B. thuringiensis using agroindustrial by product as a raw materials. This research compared the bioinsecticide production from several agroindustrial by product in solid fermentation of B. thuringiensis subsp. aizawai. This research aimed to find out the ability of B. thuringiensis subsp. aizawai using substrate combination of carbon source (cassava dregs, pulp of coffee, starch fractions of iles-iles, and sago dregs) and nitrogen source (tofu’s waste, peanut meal, palm kernel cake, and corn hominy) in bioinsecticides production using solid media cultivation. The research consisted of three stages, there were substrates characterization, microorganisms characterization, and bioinsecticides production. The main parameters to select the carbon and nitrogen sources are LC50 value and potential bioinsecticides products. The results showed that the best cultivation of B. thuringiensis subsp. aizawai contained in combination cassava dregs and palm kernel cake blends. This cultivation produced total cell counts 11.2 log CFU/g, viable spore counts 8.9 log CFU/g, LC50 0.04 μg/ ml and potential products 20000 IU/mg. Biopesticide produced can be used to kill Crocidolomia binotalis on cabbage. PRODUKSI BIOINSEKTISIDA OLEH Bacillus thuringiensis subs. aizawai PADA KULTIVASI MEDIA PADAT MENGGUNAKAN LIMBAH AGROINDUSTRI Bacillus thuringiensis subsp. aizawai merupakan salah satu bakteri yang digunakan untuk menghasilkan bioinsektisida dan digunakan pada pertanian organik untuk menggantikan pemakaian insektisida kimia. Komponen aktif yang diproduksi dari proses fermentasi B. thuringiensis subsp.aizawai adalah spora dan kristal protein δ-endotoksin, yang bersifat toksin terhadap larva Lepidoptera dan Coleoptera. Penggunaan bioinsektisida di Indonesia masih jarang karena biasanya berupa produk impor yang harganya mahal. Permasalahan ini dapat diselesaikan dengan memproduksi bioinsektisida menggunakan bahan aktif B. thuringiensis dan hasil samping agroindustri sebagai bahan baku. Penelitian ini bertujuan mengkaji kemampuan produksi B. thuringiensis subsp. aizawai pada beberapa jenis substrat sumber C (onggok, kulit kopi, fraksi pati iles-iles, dan ela sagu) dan sumber N (ampas tahu, bungkil kacang tanah, bungkil inti sawit, dan ampok jagung) dalam memproduksi bioinsektisida dari limbah agroindustri. Penelitian ini terdiri dari tiga tahap, yaitu karakterisasi substrat, karakterisasi isolat dan produksi bioinsektisida. Parameter utama untuk menetapkan sumber karbon dan nitrogen yang tepat adalah nilai LC50 dan potensi produk bioinsektisida. Hasil penelitian menunjukkan bahwa produksi bioinsektisida yang terbaik terdapat pada kultivasi B. thuringiensis subsp. aizawai menggunakan kombinasi onggok dan bungkil inti sawit. Pada kultivasi ini dihasilkan jumlah sel hidup 11.2 log CFU/g, jumlah spora 8.9 log CFU/g, nilai LC50 0.04 μg/ ml dan potensi bioinsektisida 20000 IU/mg. Bioinsektisida yang dihasilkan dapat digunakan untuk membasmi larva Croccidolomia binotalis pada tanaman kubis.